(untitled) (Indo-American Journal of Life Sciences and Biotechnology, 2025)
Colorectal cancer (CRC) was the third most common disease worldwide in 2022 and the leading cause of cancer deaths that year, and it is projected to significantly increase that number by 2040. Diet, lifestyle, and genetic factors all have a role in the cancerous development of normally functioning colonic cells, which takes a long time (usually more than ten years) and is accompanied by complicated interactions among several cellular pathways. The fact that there are significant variations in CRC incidence and death rates between demographic groupings, geographical locations, and biological sexes further supports the idea that CRC is present. Thus, a great method to lessen the burden of CRC in the next decades might be to intervene or halt the progression of the disease in high-risk groups as soon as possible. Some of the many benefits of NDSMCs—small molecule compounds generated from natural sources—include structural diversity, distinct biological activity, little toxicity, and the ability to target many targets at once. New data reveals that NDSMCs have the ability to treat colorectal cancer (CRC) by regulating apoptosis and autophagy, as well as by influencing the gut microbiota and inducing ferroptosis. Nevertheless, there is a dearth of thorough evaluations in this domain. Therefore, this study aims to give significant insights for treatment methods, preventative measures, and innovative medication development by comprehensively summarizing the research accomplishments over the last 5 years regarding the mechanisms of NDSMCs in battling CRC. We also go over the limits and clinical development of certain NDSMCs in treating CRC.